O Ministério Público na execução da pena privativa de liberdade - o desafio de garantir os direitos fundamentais dos presos - Toledo, Yashmin Crispim Baiocchi de Paula e (2010)
The Public Attorneys was created as an institution to defend the interests of sovereign will and to promote the penal prosecution. In Brazil, the Federal Constitution of 1988 conferred a new profile to the institution, by prioritizing the defense of basic human rights. The prison sentence, in turn; also appeared as an instrument of enforcing the sovereign will, directed toward transgressors of the law. Over time, it was molded and shaped according to political, economical and social changes. In the international scene, the penitentiary rights gained distinction in 1955, when the United Nations Congress elaborated the Standard Minimum Rules for the Treatment of Prisoners. Since then, the humanitarian and social idealism has made its way into the national and international legislation. The Law of Criminal Execution, Law N. 7,210/84, prior to the constitutional text, did not foresee the action of the Public Attorneys in defending the basic human rights of the prisoners. In this context, this paper proposes to investigate the performance of the Brazilian Public Attorneys through the following and inspection of the prison sentence, with the intention of verifying that it is in agreement with its new character, according to the Federal Constitution of 1988, of defending and keeping the legal order, the democratic system and the basic human rights, or if the institution continues to be engaged in the role of "relentless accuser" and in this sense is contributing to the chaos of the penitentiary system. The theoretical postulates will be centered on authors pertaining to the issue, such as: ALBERGARIA (1992); ANDRADE (2002); BARBOSA (2002); BECCARIA (1996), BITENCOURT (2001); BOBBIO (2004); CANOTILHO (1998); FOUCAULT (1987/2002); FRAGOSO (1980); MAZZILLI (2005); MIRABETE (1997/1998); ROXIN (1986/2000); SHECAIRA (1995/2004), among others.